2018
DOI: 10.1111/bjop.12309
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory versus reactive spatial attentional bias to threat

Abstract: Dot-probe or visual probe tasks (VPTs) are used extensively to measure attentional biases. A novel variant termed the cued VPT (cVPT) was developed to focus on the anticipatory component of attentional bias. This study aimed to establish an anticipatory attentional bias to threat using the cVPT and compare its split-half reliability with a typical dot-probe task. A total of 120 students performed the cVPT task and dot-probe tasks. Essentially, the cVPT uses cues that predict the location of pictorial threateni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
(68 reference statements)
1
13
0
Order By: Relevance
“…Thus, performance is not dependent on a given trial's specific exemplars, but on the predicted categories of stimuli that could have been presented. Possibly partly due to this removal of a source of variability, the cVPT has been found to have relatively good reliability (Gladwin, 2018;Gladwin, Möbius, Mcloughlin, & Tyndall, 2018). A theoretical question is what is causing the bias.…”
mentioning
confidence: 99%
“…Thus, performance is not dependent on a given trial's specific exemplars, but on the predicted categories of stimuli that could have been presented. Possibly partly due to this removal of a source of variability, the cVPT has been found to have relatively good reliability (Gladwin, 2018;Gladwin, Möbius, Mcloughlin, & Tyndall, 2018). A theoretical question is what is causing the bias.…”
mentioning
confidence: 99%
“…In the context of threat-related attentional bias, reliability was found to be improved in the cVPT relative to a usual VPT in which emotional cues were presented before probes [25]. The improved reliability was suggested to be due to the removal or mitigation of noisy influences that could play a role when actually presenting emotional stimuli, such as varying responses to particular exemplars, or potentially complex patterns of multiple cognitive responses to actually presented emotional stimuli.…”
Section: ■ Introductionmentioning
confidence: 88%
“…A Reliability of Attention Bias to Threat high reliability of around .75 was found for an alcohol-related anticipatory attentional bias (Gladwin, 2019), which could not be explained merely by individual differences involving cue features not related to their predictive value (Gladwin, Banic, Figner, et al, 2019); and which furthermore has shown correlations with risky drinking (Gladwin, 2019;Gladwin & Vink, 2018). An overall bias towards threat has been found which had relatively good reliability compared to the stimulus-evoked bias (Gladwin, Möbius, Mcloughlin, et al, 2019) and was robust to reversing the specific cues' predictive value ), but not as highin the range of .4 to .56 -as for alcohol-related bias. This may be due to use of multiple cue-probe intervals in previous work, reducing the number of trials per interval and possibly introducing a source of noise.…”
Section: Introductionmentioning
confidence: 89%